Use of Andean pseudocereals in beer production - Paucar-Menacho, Luz Maria (2022)
Beer is one of the most consumed alcoholic beverages worldwide; however, with consumers more aware of food's environmental and nutritional benefits, there is a demand for more sustainable and value-added products. Andean pseudocereals (APS) are becoming a trend as gluten-free grains with excellent nutritional and nutraceutical value. Cultivated under the extreme climate conditions of the Peruvian Andes, APS seeds are an excellent source of starch, fiber, proteins, minerals, vitamins, and bioactive compounds such as phenolic acids and flavonoids with antioxidant capacity that provide potential health benefits. This review is a compilation of the information and studies on the general characteristics and potential of the main APS as quinoa, amaranth, and cañihua for beer production. In addition, current evidence of the malting process in APS and its effects on beer's nutritional, functional, and sensory properties are also provided. Based on the research supporting the pseudocereals inclusion for the formulation of foods for celiac people, this review also looks at recent advances in applying APS to develop traditional and gluten-free (GF) beers. Finally, APS's economic, cultural, and social importance in the brewing industry is highlighted to promote the creation and innovation of fermentative products based on their bioactive compounds, thus achieving better commercial exploration of these ancestral grains.